The crime of immigration is illegal in Algerian law Between prevention and treatment - Abderrahmane, Saus Khair (Journal of Economic, Administrative and Legal Sciences, 2018)
The right to freedom of movement of human rights, which has been enshrined in the Algerian legislation and in all the statutes of their constitutions and internal laws, as enshrined in most international conventions, It achieves several benefits, must be restricted from the right of legitimacy and security and human, has no right to enter any country without in accordance with the laws of his country and the laws of the receiving country, by doing all the legal procedures necessary to move him to be a legitimate movement, In the absence of such controls, its transfer constitutes the crime of illegal immigration, whatever means used.The Algerian legislator, like other legislators, has a clear interest in the subject of the crime of illegal immigration, through several legal texts aimed at tackling this crime.It aims purely to expose to the various Algerian penal laws that criminalized the illegal immigration phenomenon and to stand at the preventive and remedial measures enacted by the legislator to confront this phenomenon.One of the findings of the researcher is that the economic, social and political factors are the most important factors that led to the increase in the frequency of illegal immigration.One of the most important recommendations is that the Algerian legislator adopt a strict and effective penal policy to address this phenomenon.
Keywords: illegal immigration; immigrant; movement; violation; procedures